PENERAPAN STRATEGI BERSAING UMKM DAN IMPLIKASINYA TERHADAP KINERJA USAHA - Sari Indah Oktanti Sembiring (Jurnal Akuntansi dan Keuangan (JAK), 2020)
SME is one of the factors affecting economic development in Indonesia right now. This research aims to study the effect of competitive strategy to bussiness performance using unique capabilities, process innovation and competitive strategy as the indicators. The sample used in this research is food and beverage SME in Lampung Province available in year 2017-2019. This research is a descriptive and verificative study, running the data using SEM-PLS. The result show that unique capabilities has a psotive and sginificant effect to business performance simultaniously and partially, and process innovation has a positive but not significant effect. The result also shows that unique capabilities and process innovation has a positive and significant effect to competitive strategy simultaniously and partially. It can be concluded that to increase Food and Beverage SME’s business performance in Lampung Province, we need to develop competitive strategy to increase the unique capabilities and process innovation